PENGARUH PELATIHAN, MOTIVASI KERJA, DAN BEBAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN HOUSEKEEPING DI HOTEL ARUSS SEMARANG - Vicky Bramasta; Enik Rahayu (Media Bina Ilmiah, 2025)
This study aims to analyze the effect of job training, work motivation, and workload on employee job satisfaction at Aruss Hotel Semarang. This topic is important to study because job satisfaction is a key factor in increasing employee productivity and loyalty in the hospitality industry. This study uses a quantitative method with a survey approach and multiple linear regression analysis techniques on 50 respondents selected through purposive sampling. The results of the study indicate that job training, work motivation, and workload simultaneously have a significant effect on employee job satisfaction with a coefficient of determination (R²) of 0.877. Partially, the three variables also have a positive and significant effect, with workload being the most dominant variable. These findings indicate the importance of balanced workload management, relevant training, and appropriate motivation in creating a conducive work environment. The results of this study provide practical contributions to Aruss Hotel management in designing more effective human resource management strategies